CONGENITAL CHOLESTEATOMA OF THE TEMPORAL BONE: ISSUES ASSOCIATED WITH ITS ETIOLOGY, DIAGNOSTICS AND TREATMENT (A LITERATURE REVIEW) - Igor’ A. Anikin; Anton D. Knyazev; Natal’ya N. Khamgushkeeva; Tat’yana A. Bokuchava (Кубанский научный медицинский вестник, 2019)
This article provides a brief literature review on congenital cholesteatoma of the temporal bone. Existing theories describing the development of this pathology are analysed. The diagnostic criteria of congenital cholesteatoma are presented, along with a comparative analysis of the characteristics of various instrumental research methods used in the verification of this disease. Issues involved with the surgical management of such patients are considered.A conclusion is made that, due to the rare occurrence of the congenital cholesteatoma of the temporal bone, diverse theories of its etiology, the lack of clear criteria for its diagnostics, this pathology requires further research to elucidate the nature of the disease and identify the risk groups of its occurrence.Conflict of interest: the authors declare no conflict of interest.